Co-doping Strategy for Developing Perovskite Oxides as Highly Efficient Electrocatalysts for Oxygen Evolution Reaction - Xu, X.; Su, Chao; Zhou, W.; Zhu, Y.; Chen, Y.; Shao, Zongping (WILEY-BLACKWELL, 2016)
A synergistic co-doping strategy is proposed to identify a series of BaCo0.9–xFexSn0.1O3–δ perovskites with tunable electrocatalytic activity for the oxygen evolution reaction (OER). Simply through tailoring the relative concentrations of less OER-active tin and iron dopants, a cubic perovskite structure (BaCo0.7Fe0.2Sn0.1O3–δ) is stabilized, showing intrinsic OER activity >1 order of magnitude larger than IrO2 and a Tafel slope of 69 mV dec−1.